Loss of LRRK2 activity induces cytoskeleton defects and oxidative stress during porcine oocyte maturation - Yu-Xia Wei; Ya-Han Wang; Xiao-Ting Yu; Lin-Lin Hu; Xiao-Qiong Luo; Shao-Chen Sun (Cell Communication and Signaling)
Abstract Leucine-rich repeat kinase 2 (LRRK2) is a ROCO family member which its mutation is closely related with Parkinson’s disease, and LRRK2 is widely involved into the regulation of autophagy, vesicle transport and neuronal proliferation. However, the roles of LRRK2 during mammalian oocyte maturation are still largely unclear. In present study, we disturbed the activity of LRRK2 and showed its essential roles in porcine oocytes. We showed that LRRK2 stably expressed during oocyte maturation, and the loss of LRRK2 activity disturbed cumulus expansion and oocyte polar body extrusion, indicating its involvement into oocyte maturation. Further analysis indicated that LRRK2 was related with cytoskeleton dynamics since its inhibition caused spindle organization defect and chromosome misalignment, and both cytoplasmic and cortex actin decreased. Moreover, LRRK2 co-localized with mitochondria and its activity was essential for mitochondria distribution. Loss of LRRK2 activity altered the TMRE level, which ultimately induced ROS-related oxidative stress. Taken together, our data suggested the important roles of LRRK2 on mammalian oocyte maturation through its effects on cytoskeleton dynamics and mitochondria functions.